A técnica violonística: Um estudo das convergências e divergências nos métodos de ensino no decorrer da história do violão - Cardoso, João Henrique Correa (2015)
Study of classical guitar technique aims at providing enabling tools to musical expression. This research investigated the different techniques in the traditional guitar methods. Our main objective was to identify the diverging and converging characteristics among such methods, as well as to elucidate elements and concepts that directly influenced the current approaches towards the instrument. For this purpose, the paper encompasses three chapters: the first one is about the structural changes in the guitar which interfered in the dawn of new technical approaches. It also presents a historical and bibliographical survey on classical guitar techniques from the 17th, 18th and 19th centuries. The second chapter identifies and discusses the main distinguishing elements of each method’s suggestions. In the last chapter, we analyse the results by using the theoretical background previously discussed, the considerations concerning to the performance possibilities and the differences learnt throughout the study of the methods. By comparing all those elements, we were able to observe that the convergences or divergences emphasizing factors among the methods are wide, being specially influenced by the didactic philosophy in each one. Eventually, we verified that the divergences are highlighted as we compare the Spanish to the Italian method.